Improving Students’ Learning Outcomes and Activities through the Implementation of the Discovery Learning Model on Mol Concept Material - Nisa, Fairuziyah Aizzatun; Dwiningsih, Kusumawati; Myranthika, Fadillah Okty (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study aims to describe the implementation of discovery learning, the responses of students which are supported by the activities carried out by students, as well as the learning outcomes of students through the implementation of discovery learning models on the mole concept material. This research is a Classroom Action Research (CAR) which was carried out for two cycles. The research subjects were 32 students in class X-3 at SMA Negeri 13 Surabaya for the 2022/2023 academic year. The data generated in this study are summarized as follows: (1) The implementation of the learning syntax of the discovery learning model in cycle 1 and cycle 2 obtained a percentage of implementation of 90.97% and 95.37% with excellent criteria. (2) The application of the discovery learning model received a positive response with a percentage of 81.25-100 so it was declared excellent and supported by a greater percentage of relevant student activities than irrelevant activities. Student activity observed in each phase of learning activities using the discovery learning model shows that the percentage of relevant activities from cycle 1 and cycle 2 gets percentages of 94.41% and 96.71%. While activities that are not relevant are 5.59% in cycle 1 and 3.29% in cycle 2. (3) In cycle 1, the learning outcomes of students who scored ≥ 75 were declared complete with a classical completeness of 78.12% and a class average score of 85.34. In cycle 2, the learning outcomes of students who scored ≥ 75 were declared complete with classical completeness of 100% and the class average score was 96.90. Based on the data obtained, it can be concluded that learning outcomes and student activity improved through the implementation of the discovery learning model.